The Use of Contextual Problems to Support Mathematical Learning - Widjaja, Wanty (Journal on Mathematics Education, 2013)
This paper examines the use of contextual problems to support mathematical learning based on current classroom practice. The use contextual problems offers some potentials to engage and motivate students in learning mathematics but it also presents some challenges for students in classrooms. Examples of the use of contextual problems from several primary classrooms in Indonesia will be discussed. Contextual problems do not lend themselves to a meaningful learning for students. Teachers need to engage students in interpreting the context in order to explore key mathematical ideas. It is critical to establish explicit links between the context and the mathematics ideas to support students' progression in their mathematical thinking.Keyword: Contestual Problems, Context, Mathematical Learning DOI: http://dx.doi.org/10.22342/jme.4.2.413.151-159